The Impact of Pinless Navigation in Conventionally Aligned Total Knee Arthroplasty - P. Koenen; M. M. Schneider; T. R. Pfeiffer; B. Bouillon; H. Bäthis (Advances in Orthopedics)
Background. Restoration of the mechanical axis is a main objective in total knee replacement (TKR). Aim of this study was to analyse the verification tool of a pinless navigation system in conventional TKR (cTKR). Methods. In a prospective study, 147 TKR were performed by conventional technique. Using the “pinless verification” mode of a smartphone based navigation system, the cutting block position and final resection plane for distal femur and proximal tibial resection were measured. If necessary, the block position or resection level were optimized, corrections were protocolled. Postoperatively, standardized radiographs were performed. Results. In 65.3%, intraoperative measurements changed the surgical procedure (corrections: 20.4% femoral, 25.9% tibial, 19% both). The additional time for surgery compared to cTKR averaged 6 minutes (79 ± 15 versus 73 ± 17 minutes). Using navigation data, the final femoral and tibial axes were in 93% within a range of ±2°. A mean difference of 1.4° and 1.6° could be shown between the final measurement of the navigation system and the postoperative mLDFA and mMPTA. Conclusion. Intraoperative pinless navigation has impact on the surgical procedure in the majority of cTKR. It represents a less time-consuming tool to improve implant position while maintaining the routine of conventional technique.